Readability Level of Reading Texts in The English Textbook Published by Intan Pariwara for Junior High School Grade IX at Junior High School 2 Grogol Kediri - Kurnia Puspita Pitriani Darwin (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2022)
This study describes the results of research regarding: (1) The types of text listed in the English textbooks used by the teacher are books published by Intan Pariwara, (2) The level of readability of books used by teachers published by Intan Pariwara in class IX in SMAN Grogol 2 Kediri. This research uses descriptive qualitative as a research technique. The method used in this research is interviews with English teachers, calculations with FRY graph formulas, and documentation. The research results obtained are: (1) The types of text found in the English book entitled Bahasa Inggris published by Intan Pariwara are announcement text, advertisement text, procedure text, report text, descriptive text, narrative text, and recount text. (2) for the calculation of the readability level using the FRY graph formula, the researcher gave a limit to the type of text used for the study, namely Narrative text with a total of two reading texts and Report text with a total of two reading texts. The results obtained have different numbers, namely from those that are too easy or not according to the user level, namely for class VII, for class VIII, and there is one text that corresponds to the user level, namely for class IX, and one text for class X.